2009
DOI: 10.1007/s00404-009-1253-3
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord blood amino-terminal pro-brain natriuretic peptide levels according to the mode of delivery

Abstract: Vaginal delivery did not result in increased cord blood NT-proBNP levels reflecting cardiovascular stress to the fetal heart. NT-proBNP was inversely correlated with gestational age. Low Apgar score and umbilical cord blood pH appeared to induce the fetus to produce increased amounts of NT-proBNP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…Based on the umbilical cord blood analysis, Won Joon et al concluded that stressful intrauterine environment may stimulate fetuses to synthesize NT-proBNP. According to the same authors, vaginal delivery is not associated with an increase in umbilical cord blood NT-proBNP levels and consequently, does not promote a fetal cardiac stress [ 35 ].In our present study, serum concentration of NT-proBNP did not show significant associations with parity and route of delivery. Moreover, NT-proBNP levels were not modulated by participants’ age, gestational age at delivery, birth weight and pH of the umbilical cord blood.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the umbilical cord blood analysis, Won Joon et al concluded that stressful intrauterine environment may stimulate fetuses to synthesize NT-proBNP. According to the same authors, vaginal delivery is not associated with an increase in umbilical cord blood NT-proBNP levels and consequently, does not promote a fetal cardiac stress [ 35 ].In our present study, serum concentration of NT-proBNP did not show significant associations with parity and route of delivery. Moreover, NT-proBNP levels were not modulated by participants’ age, gestational age at delivery, birth weight and pH of the umbilical cord blood.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with term pregnancy, NT‐proBNP concentrations were higher during earlier stages of gestation (mean, 1998 ng/L; median, 1874 ng/L; 95% CI, 242–3754 ng/L) (Figure ). The decrease with advancing gestation has also been confirmed for umbilical cord blood samples. It may be the consequence of myocardial maturation, which includes an increase in compliance and relaxation time, a decrease in afterload and an improvement in systolic function.…”
Section: Natriuretic Peptides: Fetal and Neonatal Physiology And Metamentioning
confidence: 59%
“…Bar‐Oz et al . and Seong et al . did not find an association between mode of delivery and umbilical cord blood NT‐proBNP concentration, while Fortunato et al .…”
Section: Natriuretic Peptides: Fetal and Neonatal Physiology And Metamentioning
confidence: 90%
“…BNP and NT-proBNP concentrations rise at birth in normal healthy infants, level off at 3-4 d, and then fall steadily to stable but low levels in infancy (12,16). In several studies, the method of delivery of the newborn did not influence natriuretic peptide levels (17,18). However, Fortunato et al reported that NT-proBNP was significantly higher in infants delivered by elective cesarean section than in infants delivered after spontaneous birth.…”
Section: Natriuretic Peptidesmentioning
confidence: 99%
“…Fetal myocardial compromise resulted in a distribution of cardiac output toward the left ventricle and a rise in the right-ventricular afterload, explaining the increase in ANP (38). Seong et al, in a study to evaluate the relationship between NT-proBNP levels and the method of delivery, found that infants with low Apgar scores and low umbilical cord blood pH appeared to have increased levels of NT-proBNP (18). Elevation in cardiac troponin levels is much less common in the perinatal period.…”
Section: Clinical Indicationsmentioning
confidence: 99%